(untitled) (International Journal of Technology and Management Research, 2020)
This study examined the effects of subordinates’ perception of supervisor favouritism on subordinates’ commitment to their organizations in the Ghanaian context. A cross-sectional survey was employed to study 296 employees comprising supervisors and subordinates in two organizations (public and private). Results from t-test, analysis of variance, Pearson product-moment correlation coefficient and hierarchical multiple regression showed: (a) no significant difference in the amount of perceived supervisory support; (b) that perceived favouritism based on ethnicity had a greater tendency to influence supervisor-subordinate exchanges and also the amount of perceived supervisory support; and (c) that subordinates who received more supervisory support were highly committed. There was an inverse relationship between perceived favouritism and organizational commitment of subordinates. Surprisingly, subordinates who perceived favouritism did not show a higher tendency to quit their organizations but rather continued to stay. The organizations could benefit greatly if the lower turnover intents are translated into practical work outputs but that, of course, will involve reducing perceived favouritism to the barest minimum. Suggestions for future research are made. Keywords: Supervisor-subordinates relations; Organizational commitment; Ethnicity